1994
DOI: 10.1002/polb.1994.090320310
|View full text |Cite
|
Sign up to set email alerts
|

Toluene diffusion in butyl rubber

Abstract: The sorption isotherm and the polymer mass‐fixed diffusion coefficients, D, for toluene in butyl rubber have been measured by the incremental sorption method to concentrations of 130%, corresponding to a solvent volume fraction of 0.578. The increase in D with concentration is strongly exponential to a concentration of 30% and then begins to level out. Since the nature of the dimensional change occurring in vapor sorption was not known, the values of D were converted to solvent self‐diffusion coefficients, D1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…This simple theory has been tested and found to describe satisfactorily the diffusion of a number of organic liquids and vapours in polymer solutions 14. Recently, Schneider et al 15 have shown that the diffusion of toluene in butyl rubber follows the predictions of the Fujita's free‐volume theory 11. 13 It should be noted here that, in these studies, the free‐volume of the polymers was obtained through indirect methods.…”
Section: Introductionmentioning
confidence: 99%
“…This simple theory has been tested and found to describe satisfactorily the diffusion of a number of organic liquids and vapours in polymer solutions 14. Recently, Schneider et al 15 have shown that the diffusion of toluene in butyl rubber follows the predictions of the Fujita's free‐volume theory 11. 13 It should be noted here that, in these studies, the free‐volume of the polymers was obtained through indirect methods.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, we tried to fit the experimental results using Eq. (8). It showed us that Eq.…”
Section: Sorption Kineticsmentioning
confidence: 98%
“…The parameter A d depends mainly on the size of the diffusant while B d depends on the minimum volume required for the displacement of the diffusant. Since diffusion depends on the chemical structure of the polymer and the size of the diffusant molecules, understanding of the diffusion mechanism is usually done through the application of Fick's laws and its modified versions from which one can obtain information on the rate of diffusion and the polymer segmental relaxation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The sorption isotherms showing mass-time curves are plotted in Fig. 1 for four different weight percents of sulphur indicated in the Figure. At the equilibrium mass values, the value of the network chain density was calculated for each sulfur concentration in the network via the modified Flory-Rehner equation [8,17].…”
Section: Swelling Measurementsmentioning
confidence: 99%